INCULCATING THE ESSENCE OF ‘WASATIYYAH’ IN MUSLIM SOCIETY: THE STATE PROMOTION AND MUSLIM INTELLIGENTSIA RESPONSES IN MALAYSIA - Othman, Mohammad Redzuan; Sulaiman, Mashitah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
Unlike many Middle Eastern countries which face drastic changes and upheaval from mass riots which express undesirable protest against the established status quo, the Malaysian government’s response to da‘wah movements since the early developmental stage of the Islamic resurgence in the 1970’s to 1980’s can be categorized into three responses, namely, confrontation, cooptation and accommodation. Recently, in June 2011, the government launched its official slogan of “Wasatiyyah” or moderation to revitalize its legitimacy for the purpose of gaining support from the Malay-Muslims by applying the Islamic concept of moderation in handling the challenge of religious extremism and Islamic resurgence at the national level, as well as championing this issue in the global arena. This paper discusses the concept of moderation in Islam or wasatiyyah as elucidated by al-Quran and as-Sunnah, as being the primary sources, Islam, and compares them with the slogan of Wasatiyyah as promulgated by the Malaysian government. This paper also analyzes the establishment’s or ruling party’s campaign to popularize the concept of moderation and strengthen its role to represent the Muslims’ aspiration for the country against its traditional competitor, Pan-Malaysian Islamic Party (PAS), which is typically known for its so-called “extreme demand to implement the Sharī‘ah laws” , namely Hudud Laws, and establish an Islamic state. The concept of moderation introduced by the government has been described through various government official institutions, new media of mass communication or social networks and websites. As expected from the beginning of its pronouncement, PAS response to the state campaign of this religious slogan is predictable. In response to this commonly well-known concept in Islam, Wasatiyyah or the concept of moderation, has been extensively discussed and has become the main topic in seminars, colloquiums and conferences by Muslim intelligentsia and scholars. This study employs content analysis of leaders’ speeches in newspapers, official reports, government websites; and secondary sources, uses methods of observation and interview to evaluate the slogan used by the state, and examines feedback from the opposition and intellectuals. Reactions of Muslim intelligentsia and scholars may reflect psychological support of this knowledgeable group of people for the established regime which could influence the majority’s acceptance.